1983
DOI: 10.1073/pnas.80.16.5032
|View full text |Cite
|
Sign up to set email alerts
|

Association of endogenous viral loci with genes encoding murine histocompatibility and lymphocyte differentiation antigens.

Abstract: Several polymorphic DNA restriction endonuclease fragments hybridizing with xenotropic and ecotropic envelope virus probes map adjacent to minor histocompatibility and lymphocyte (H/Ly) antigen-encoding loci. Viral DNA restriction fragments are associated with Ly-17 on chromosome 1, H-30, H-3, and H-13 on chromosome 2, Ly-21 on chromosome 7, H-28 on chromosome 3, and H-38 (chromosomal location as yet undetermined). In each case no recombinant can be found between the H/Ly locus in question and the virus-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Since such expression might be markedly affected by both alterations in methylation and rearrangements of class I genes, these changes might play an important role in resistance to disease. Similar mechanisms (19,20), the data in this paper are consistent with the possibility that type C RNA viruses may interact with histocompatibility genes to alter their expression in a physiologically important manner. …”
Section: Discussionsupporting
confidence: 77%
“…Since such expression might be markedly affected by both alterations in methylation and rearrangements of class I genes, these changes might play an important role in resistance to disease. Similar mechanisms (19,20), the data in this paper are consistent with the possibility that type C RNA viruses may interact with histocompatibility genes to alter their expression in a physiologically important manner. …”
Section: Discussionsupporting
confidence: 77%
“…Retroviral loci account for as much as 0.1-0.5% of the total mouse genome and a significant number of these endogenous proviral loci are found in linkage with genes that encode histocompatibility and lymphocyte differentiation antigens (52,53). Furthermore, it has recently been demonstrated that endogenous Mtv retroviral sequences are homologous to Mls (minor lymphocyte stimulatory) superantigens and thus serve to alter the T cell repertoire (54)(55)(56)(57) …”
Section: Resultsmentioning
confidence: 99%
“…Precedent for the control of virus expression by flanking sequences comes from studies of Mov expression (Jaenisch et al, 1981) and from transfection studies (Cooper & Silverman, 1978;Copeland & Cooper, 1979). Recent studies using recombinant inbred strains of mice have placed a variety of endogenous viruses in the vicinity of lymphocyte differentiation antigens (Blatt et al, 1983;Meruelo et al, 1983). By molecularly cloning the integrated proviruses of BXV and BDV, both of which are expressed in differentiating B-cells, we expect the flanking sequences to contain interesting probes for studying the expression of genes important for B-cell development in addition to facilitating molecular studies on the control of the retrovirus sequences.…”
Section: Discussionmentioning
confidence: 99%